An empirical analysis of bundling and tying : over-the-counter pain relief and cold medicines - David S. Evans; Michael Salinger (Center for Economic Studies and ifo Institute (CESifo), 2004)
We apply and extend the cost-based approach to bundling and tying under competition developed in Evans and Salinger (2004a) to over-the-counter pain relievers and cold medicines. We document that consumers pay much less for tablets with multiple ingredients than they would to buy tablets with each ingredient separately. We then decompose the sources of these savings into marginal cost savings and a component that reflects fixed costs of product offerings. The analysis both documents substantial economies of bundling and illustrates the sort of cost analysis that is necessary for understanding tying.
Keywords: L11; 330; Rezeptfreies Arzneimittel; Preis; Price bundling; Verbundvorteil; Grenzkosten; Schätzung; Vereinigte Staaten